When Prisoners Had a Union: The Canadian Food and Allied Workers Union Local 240 - House, Jordan (Labour / Le Travail, 2018)
Most Canadian prisoners work, yet very little attention has been paid to them as workers by either labour scholars or unions. However, in 1977 the Canadian Food and Allied Workers union (cfaw) organized both incarcerated and non-incarcerated meat cutters into the country's first and only legally recognized union representing primarily prisoners, cfaw Local 240. The union drive came in response to the Ontario government's push to increase prisoners' participation in the workforce, including the introduction of a number of “outside managed industrial programs,” which involved private firms operating within provincial correctional facilities. These privately managed industries rekindled some older debates around the potential for prison labour to undermine the wages of free labour, but in the case of the experimental abattoir program at Guelph, they also resulted in something new: unionized prisoners. The union not only made important gains for the workers, but also made modest gains for prisoners' rights. While cfaw Local 240 would eventually be merged into subsequent unions, it continues to serve as a model for working prisoners and represents a rare moment in Canadian history – one where a union organized prison labour instead of opposing it.